Pengaplikasian Pembelajaran Berbasis Kehidupan guna Mendukung Aktivitas Belajar - Zahid Zufar At Thaariq (Balitbangda Provinsi Lampung, 2021)
Information and Communication Technology (ICT) has experienced rapid development, causing various changes in all fields, especially education. Education is the basic key of human resource development. So, one of the keys to quality education lies in the application of the teaching and learning process that is carried out. The application at this time can be said to have great potential. This is because with the assistance of ICT, various accesses to learning tend to be unlimited. This provision is very important in empowering qualified and superior students. For this reason, the authors are interested in studying life-based learning as a solution in supporting learning activities in the current era of openness. It is necessary to note that life-based learning is a learning concept that emphasizes real life, so it is not only oriented towards learning that is static, but also dynamic and temporary. The hope is that through this paper it can be an alternative reference in the development of learning or subsequent research development.